Wieczorowe szkoły podstawowe dla pracujących w Gdańsku ogłaszają zapisy. (Gdańsk-Wrzeszcz : [s.n.], 1966)
Afisz inf. o zapisach.
Keywords: Szkoły -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne